PENGEMBANGAN DAN EVALUASI MEDIA KAHOOT SEBAGAI MODUL PEMBELAJARAN PADA MATERI SIFAT-SIFAT TERCELA DI MAN 1 PLUS KETERAMPILAN BENGKALIS - Gusti Erlina; Rian Vebrianto (Institut Agama Islam Hamzanwadi NW Lombok Timur, 2025)
Learning using media is an important component in the teaching and learning process. For this reason, researchers want to develop learning media in the form of modules on Kahoot! with the theme of despicable traits for Madrasah Aliyah MAN 1 Plus Bengkalis Skills level. The methodology used in this research is research and development (R&D) involving 34 teachers and 50 class X students where the data collection process was taken directly by researchers using an instrument in the form of a media assessment questionnaire which explains the media module on Kahoot and then asks respondents to answer and assess the quality of the media. The data obtained was analyzed using descriptive analysis. The results of the research show that the value of the learning media components assessed by teachers (N=34 ; sd = 0.124.) in the very feasible category. So learning using Kahoot media! can be used as a tool for conveying information so that learning can run well and students can learn in a pleasant atmosphere.